2004
DOI: 10.1111/j.1740-8261.2004.04006.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis of the cranial cavity and caudal cranial fossa in the dog: a computerized tomographic study

Abstract: This investigation was initiated to develop a reliable and simple computerized tomography (CT) method for evaluating the morphometry of the cranial cavity (CC) and caudal cranial fossa in the dog. We obtained linear, area, and volume measurements of the entire CC and the caudal fossa compartment in 24 dogs, using transverse and reformatted sagittal and dorsal CT images. The ratios between the CC and the caudal fossa volumes were calculated, as were the ratios between the CC and caudal fossa midsagittal (MS) ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 18 publications
2
26
0
Order By: Relevance
“…Computed tomography allows evaluation of single image slices in different scanning planes and the use of specialised software additionally allows accurate linear and volumetric measurements to be obtained. Morphometric cranial measurements using CT have been described in dogs [17,18], and more recently volumetric measurements of normal equine paranasal sinuses were calculated from 3-dimensional reformatted rendering of CT slices using commercial software (Amira TM ) [4]. However, minimal imaging information has been reported on the anatomy of normal or diseased nasal conchal bullae.…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography allows evaluation of single image slices in different scanning planes and the use of specialised software additionally allows accurate linear and volumetric measurements to be obtained. Morphometric cranial measurements using CT have been described in dogs [17,18], and more recently volumetric measurements of normal equine paranasal sinuses were calculated from 3-dimensional reformatted rendering of CT slices using commercial software (Amira TM ) [4]. However, minimal imaging information has been reported on the anatomy of normal or diseased nasal conchal bullae.…”
Section: Discussionmentioning
confidence: 99%
“…The second goal of the study was to measure, in this clinically normal population, the standard CT dimensions of the caudal fossa; these measurements were calculated in different breeds in a previous study (Garcia‐Real and others 2004). Our data are detailed in the Results section.…”
Section: Discussionmentioning
confidence: 99%
“…Original CT data were transferred as DICOM images to an image analysis workstation (Osirix v 2.5.1, Dicom Pacs Workstation, http://www.homepage.mac.com/rossetantoine/osirix/). In the sagittal plane, linear dimensions starting from the dorsum sellae were measured as previously described (Garcia‐Real and others 2004): dorsum sellae to cranial aspect of the most dorsal part of the foramen magnum (CdF ds‐crdfm) and dorsum sellae to caudal aspect of the most ventral part of the foramen magnum (CdF ds‐vfm); height of the foramen magnum was also measured (CdF hfm) (Fig 3A). The area of the caudal fossa was calculated (CdF MS area) (Fig 3B).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, concurrent neural disease is commonly identified in dogs undergoing imaging because of CLM. 1,[27][28][29] Studies have identified positive associations between the caudal fossa volumeto-total cranial volume ratio and neurologic signs, 1 between volume ratios and linear measurements, 28 and between decreased caudal fossa volume and syringomyelia. 25,26 Techniques have been reported that use linear and 3-D measurements of MR and CT images to determine total brain volume, total cranial volume, and cranial and caudal fossa volumes.…”
mentioning
confidence: 99%